Traditional Herb Used and Training on Preparation Moringa oleifera Lam. Herb as Dip and Capsules - Yufri Aldi; Salman Umar; Aditya Alqamal Alianta; Elidahanum Husni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Moringa leaves have grown abundantly in the 50 Kota Regency area. Studies have been carried out regarding moringa leaves, and research has shown that moringa leaves are effective as a medicine to increase the body's immunity. The community needs to know and understand the benefits of Moringa leaves. Based on that circumstance, the Community Service regarding how to process the Moringa leave to be dip preparation and capsule has been conducted in Jorong Padang Kandis, VII Koto Talago Sub-district, Guguk District, 50 Kota Regency, West Sumatra. The activity was carried out on 19 August 2023. The participants were the Family Welfare Movement (PKK) and Bundo Kandung groups in Jorong Padang Kandis, attended by 100 participants. The method was lectures and training on preparing Moringa herb leaf preparations and making Moringa leaf capsules, which the community can use directly. Community services topics were